Big Five Personality Traits and Life Satisfaction: The Mediating Role of Religiosity - Szczesniak, Malgorzata (Religions, 2019)
Extensive empirical research conducted up till now has confirmed that personality represents one of the most significant predictors of life satisfaction. Still, no studies to date have empirically tested the path of influence from personality traits to religiosity and the effects of both on life satisfaction/positivity within the same model. In the current study, we aimed to verify whether the relationship between personality and satisfaction/positivity was mediated by religiousness, as it is considered motivational in nature. The sample consisted of 213 participants (72% women) aged between 18 and 75. The average age was approx. 32. We used the following tools: the NEO Five Factor Inventory, the Satisfaction with Life Scale, the Positivity Scale, the Personal Religiousness Scale, and the Intensity of Religious Attitude Scale. Our hypotheses (H1 and H2) found their confirmation to a large degree. In fact, life satisfaction positively correlated with extraversion, agreeableness, and conscientiousness. Moreover, life satisfaction negatively correlated with neuroticism. A similar pattern of results, even slightly stronger, was found in the case of positivity and personality traits. Contrary to our assumptions, neither life satisfaction nor positivity correlated with openness to experience. Extraversion and agreeableness correlated positively with religious attitude, personal religiousness and its four dimensions. Conscientiousness correlated positively only with faith, personal religiousness, and religious attitude. We also found negative and significant correlations between openness and all of the dimensions of personal religiousness. A lack of correlation was found between: (1) neuroticism and all of the dimensions of religiosity; (2) conscientiousness and religious practices, and religious self. Our research offers a contribution to the field by providing evidence that some personality traits predict life satisfaction/positivity because respondents display a personal religiousness/religious attitude.